An examination of newspapers' role in English language learning in Pakistan: Issues and recommendations - Khan, Jamila (Universitas Islam Negeri Banda Aceh, 2023)
Pakistan is a developing nation characterized by its lower income, turbulent economy, elevated commodity prices, and escalated inflation. The government sector's progression has been disappointingly inadequate due to limited resources and a meager budget allocation for education. In light of these prevailing circumstances, this article endeavors to illuminate the newspaper as an economical and invaluable source of diverse information that can be utilized as authentic material for enhancing the teaching and learning of languages, particularly English. The article underscores the significance and affordability of newspapers in primary and secondary educational institutions, specifically public schools, within the context of Pakistan. A comparative analysis of Pakistan's literacy rate vis-à-vis other countries in the region and the substitution of English newspapers for English readers to ameliorate English language acquisition are deliberated upon. Additionally, the article scrutinizes the budgetary allocation for the educational sector in Pakistan from 2017 to the present year, as well as the price range of English readers from this vantage point. Given the significance of the English language and the challenges associated with its instruction and acquisition, this paper proffers several recommendations for the integration of newspapers into primary and secondary levels at public schools.